Labor market situation of refugees in Europe: The role of individual and contextual factors - Kosyakova, Yuliya; Kogan, Irena (Frontiers in Political Science, 2022)
The paper sheds light on the patterns of labor market integration of refugees in Western countries, who arrived primarily during the 2015–2016 mass refugee migration. Its major focus lies on the role of individual and contextual factors responsible for refugees' success in the labor market. At the host country level, the extent of permeability along the ethnic lines and the welcome of reception—both on the part of the majority population and the part of the established minorities—constitute further essential moderators of refugees' labor market success. This comprehensive literature overview draws on the flourishing body of research in Europe and beyond and discusses commonalities and differences across refugee origins and destinations while paying particular attention to the time trends and meaningful heterogeneities along with refugees' socio-demographic characteristics. We conclude by identifying major avenues for future research.